The psychological impact of the menstrual cycle on athletic performance - Gilmour, S. (SportRxiv Preprints, 2025)
This study investigates the psychological impact of the menstrual cycle (MC) on athletic performance among 50 professional, national, and regional-level female athletes in France, representing nine sports disciplines; rugby, football, track and field, volleyball, basketball, fencing, triathlon, swim-run, and water polo. Participants completed a 30-item questionnaire assessing the perceived influence of their MC on training and competition, followed by semi structured interviews with a subset of participants to delve deeper into their experiences. The study focused on four thematic areas: medical approach and menstrual tracking, relationship with coaches, perception of MC impact on performance, and the extent of its influence on outcomes. Findings reveal that MC-related psychological fluctuations— manifesting as shifts in motivation, focus, effort thresholds, and levels of stress and anxiety—significantly impact performance perception. However, menstrual tracking and its integration into training regimens remain inconsistent. The study highlights the need for sports organizations and coaches to address the MC's psychological effects in athlete care, promoting tailored training strategies to enhance well being and performance. Future research should integrate hormonal and psychological assessments to clarify correlations between MC phases and performance and explore effective interventions for managing the MC`s impact in sports contexts.